Assessment of Smoothed Particle Hydrodynamics (SPH) models for predicting wall heat transfer rate at complex boundary - Ng K.C.; Ng Y.L.; Sheu T.W.H.; Alexiadis A. (Elsevier Ltd, 2023)
Boundary conditions; Heat transfer; Least squares approximations; Natural convection; Boundary condition treatments; Dirichlet boundary condition; Moving least squares; Numerical solution; Reasonable accuracy; Smoothed particle hydrodynamics; Unsteady natural convection; Weakly compressible; Hydrodynamics